The Efforts of Islamic Splinter Movements to Withstand from Heretical Issue in Indonesia: Study of LDII, MTA and Jam'iyyatul Islamiyah - Zaki Faddad Syarif Zain; Anggi Wahyu Ari (Jurnal Studi Sosial dan Politik, 2019)
This article discusses how the splinter movements in Indonesia, namely LDII (Lembaga Dakwah Islam Indonesia), MTA (Majlis Tafsir Al Quran) and JMI (Jam'iyyatul Islamiyah) can survive and develop against two constraints that are the state and Islamic orthodox group. The methods of this research-based article are both library and field research. This article uses comparative analysis from the three movements include their adaptive means to the social and political milieu in Indonesia. The movements start to grow in the 1970'. In New Order Era (1966-1998), under Suharto authoritarian regime, these movements use the state approach by joining Golkar, government political party, and help the party to win general elections. However, in the 1990 era, when Suharto starts to embrace the orthodox group, government protection to those religious groups is not enough to withstand the heretical issues that have already spread in public. The issues lead to physical persecution from the mass to these movements. Thus, the only way to survive from that conditions, the three movements start to make an approach to orthodox groups, especially MUI (Majlis Ulama Indonesia) the mainstream group representative such as NU (Nahdlatul Ulama) and Muhammadiyah two biggest Islamic groups in Indonesia, by making dialogues and complying the Islamic mainstream standards issued by MUI.